FAKTOR RISIKO SINDROM METABOLIK PADA PEKERJA: SISTEMATIK REVIEW - Atie Umnia Najikh; Henny Permatasari (Poltekkes Kemenkes Bandung, 2023)
Many factors influence metabolic syndromes, workers are one of the groups that are prone to metabolic syndrome. The purpose of this review is to identify and describe the relationship between physical activity habits, diet patterns, rest patterns, stress levels, and smoking habits with the incidence of metabolic syndrome in workers. A systematic literature review based on PRISMA guidelines using articles from ProQuest, ScienceDirect, and Clinical Key Nursing with the criteria for articles published in the last five years from 2018-2022, using English and full text with abstracts. A total of 198 articles were obtained, after screening the title and abstract obtained, 27 articles, then 18 articles were issued after going through the selection of the full text and suitability of the topic. At the end of the selection, 7 articles will be involved in the analysis process. Occupational stress factors and dietary patterns influence the increased risk of metabolic syndrome in workers, further research using a broader type of literature and varied types of labor needs to be carried out to get a broader picture of the factors causing metabolic disorders in workers.